Evaluation of the digital gap of the Urabá antioqueño cocoa farmer - Toro Beleño , Luis Felipe; Zapata Guzmán , Jaime Enrique (Revista Colombiana de Investigaciones Agroindustriales, 2021)
Cocoa is an important crop in the Colombian agricultural sector due to the productive chain with the agro-industry, the social impact and the appreciation of the world market for chocolates, confectionery and others; which is found in high percentage in the hands of small and medium farmers scattered throughout various regions of the country, in many cases in remote areas with a low technological level, to which the use of technological innovations from Digital Agriculture (AD) of the SENA project Cacao 4.0 would serve to increase competitiveness and thereby improve the farmer’s quality of life, but it is necessary for them to have access to these innovations. Based on this access, the connectivity and electronic literacy of cocoa farmers in the Urabá Antioqueño area was evaluated in the field, measuring coverage, access and use of the internet in general. Low values ​​were found in each of them, consistent with those mentioned in the literature for the rural sector of Colombia and Latin America. Based on the results obtained, a 67% digital gap index was established, where internet use is the most lagging indicator and mobile internet access with a value close to 70%.